Modificacion del Capítulo 4 titulo 3 de la ley orgánica de servicio Publico-Losep, para que el Ministerio de Relaciones Laborales, como ente rector de la politica laboral y organismo imparcial, conozca y resuelva los sumarios administrativos planteados en contra de las o los servidores publicos - Moran Sani, Maritza Alexandra (2015)
Since the promulgation of the Constitution of Montecristi, the Republic of Ecuador change their view of the State, a State Constitutional Rights and Social Justice. Within this new approach of State, the National Assembly introduced major reforms in the workplace issuing laws, especially "for regular" employment relationships with organizations and institutions of the Public Sector. The Organic Law of Public Service - LOSEP, and its General Regulations, are the legal manuals, which normalize the operation of human resources in the public sector entities to apply the penalties or civil servants, for disciplinary actions; According to these statutory bodies should establish the administrative proceedings, by the Unit Human Resource Management - UATH, which inform the appointing authority, who have the conformity of starting the Administrative Summary or file, it must be motivated and grounded, this detail of the process I can see that the sanctioning body is the same appointing authority as head of the institution to which the public servant sumariado belongs. Considering that the Constitution of the Republic of Ecuador guarantees every citizen "to be tried by a judge or independent, impartial and competent judge. No one shall be tried by special courts or by special commissions created to the effect, "this constitutional guarantee, in the exercise of rights of public servants is not being fulfilled. As a servant publishes and having found this problematic decided preparing this research paper entitled: "MODIFICATION OF CHAPTER 4 PART 3 OF THE ORGANIC LAW PUBLIC SERVICE LOSEP, THAT THE MINISTRY OF LABOUR RELATIONS AS A GOVERNING BODY OF POLITICAL WORK AND FAIR umbrella organization, LEARN AND MEET THE SUMMARIES ADMINISTRATIVE RAISED AGAINST THE PUBLIC SERVANTS OR ". As part of this research, we perform a doctrinal and legal analysis of the issues raised, to expose the insolvency of the LOSEP and the urgent need for administrative inquiries are known, addressed and resolved within the Ministry of Labor Relations. This work collects theoretical arguments, results of field research, the analysis demonstrates the need to generate impartiality when substantiate administrative proceedings, raised against or public servants.